The Audiences of Poetry: Forms of Verse Literariness in 2000s Italy (Altre Modernità, 2025)
While occasional moments of openness and shifts within the traditional ‘poetry audience’ were not absent in the last century, it was in the early 2000s that poetry began expanding into middle-brow and even low-brow circuits with unprecedented intensity. The rise of a distinctly successful poetic production, aimed at diverse audience segments – often far less specialized than traditional poetry readers – has become an increasingly visible phenomenon. This trend spans from the sentimental, saccharine verses of instapoets such as Gio Evan and Francesco Sole to the playful, cabaret-like poetry of Guido Catalano. It also includes authors like Candiani, Arminio, Gualtieri, and Vivinetto. This study explores the reasons behind this shift and maps its different forms of expression. It adopts a functionalist approach inspired by Vittorio Spinazzola’s thought and Pierre Bourdieu’s sociology. First, it classifies authors and texts according to their target audiences. Then, it examines the aesthetic premises of sub-institutional poetry, comparing them with the values that shape legitimate poetry. Finally, it analyzes this poetry’s stylistic features, emphasizing its tendency toward epideixis, oratory, and sentimental expression.
Keywords: contemporary italian poetry; poetry audience; sociology of literature; low-brow poetry; Popular aesthetics